Pathology of Asbestos-Associated Diseases - Roggli, Victor L.; Sporn, Thomas A.; Oury, Tim D. (Springer New York, 2004)
Pathology of Asbestos-Associated Diseases integrates the newest research and advances in its discussion of asbestos-induced diseases. Organized in 13 chapters, the book begins with background information on the mineralogy of asbestos, occupation and environmental exposure to asbestos, and asbestosis. A detailed discussion on mesothelioma includes a historical background, addresses etiologic considerations and epidemiology, pathologic features, differential diagnosis and treatment and prognosis. Guidelines for assessing and identifying asbestos-associated carcinomas of the lung, including histopathology and differential diagnosis, are discussed. The text also addresses the explosion of research in the area of molecular biology and the abundance of information bearing on the mechanisms by which asbestos causes disease. Chapters also cover cytopathology and experimental models of asbestos-related diseases. The diseases associated with asbestos have significant medico-legal implications, and there are two chapters dedicated to addressing the issue. More than 190 illustrations complement the text. An invaluable reference for the pathologist, pulmonologist, radiologist, and occupational medical practitioner interested in asbestos-related disease as well as malpractice attorneys needing an understanding of asbestos, the diseases it induces, prognosis and clinical implications.